Natural disasters and gross domestic product: panel data approach for five selected South Asian countries - Lee, Chin Yu; Abdul Samad, Abdul Rahim (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study investigates the long-run relationship between natural disaster and gross domestic product (GDP) using panel data from year 1991 to 2009 based on five selected South Asian countries. The result indicates that natural disasters have a negative impact on GDP, while investment has a positive impact on GDP. Given that the impact of damage due to natural disasters is greater than the impact of investment to GDP, therefore, research on the impacts of natural disasters needs great attention.